Encouraging the Participation of Small Business and Private Entrepreneurship in Providing Employment - Egamberdiyev Rahmonjon Ilhomovich (International Journal on Integrated Education, 2024)
In the article, the role and characteristics of small business in ensuring employment of the labor force, the role of small business enterprises as employers in the labor market, the reasons for the stonger tendency to ctreate new jobs in small business entities compared to large enterprises in developed countries briefly analyzed on the example of experience and the main reasons that hinder the development of entrepreneurship are indicated.